Influence of chronic obstructive pulmonary disease on health status of the population of Ukraine - V. Mikhalchuk; A. Vasyliev (Kazimierz Wielki University, 2017)
Chronic obstructive pulmonary disease in medical, social and economic context is one of the main causes of morbidity and mortality worldwide due to premature mortality from COPD and associated complications. The purpose of our study was to analyze the current epidemiological state of chronic obstructive pulmonary disease inUkraineand worldwide and to determine the priority trends for COPD diagnosis. Main part. According to international literature data, COPD currently affects between 8% and 22% of adults over the age of 40. COPD is ranked 4th cause globally among all causes of death, according to researchers, COPD will be ranked fifth cause in terms of morbidity and third in the structure of mortality causes in the world by 2020. The largest meta-analysis, which estimates the prevalence of COPD in Europe, has shown that the disease affects more than 44 million people, or about 7.4% of the population inEurope. InUkraine, the prevalence of COPD is 236.1 persons per 10,000 population, and the incidence is 20.08 per 10,000 people. According to the "European White Paper on Lungs" (2003)Ukraineis one of the countries with the highest mortality rate of COPD - 749 cases per 100,000 population. This is primarily due to late detection of COPD, only 25% of cases are diagnosed at early stages of disease. Conclusions COPD is one of the most severe inflammatory diseases of the respiratory tract with constantly increasing prevalence, which leads to an increase in the disability rates in able-bodied population. The importance of early diagnosis of COPD is indisputable. Today general practitioners - family doctors should play a key role in timely detection and prevention of COPD, which will preserve population health, reduce premature mortality, increase life expectancy, and generally improve public health inUkraine.